Transforming MSMEs in Digital Villages: Enhancing Legality, Financial Literacy, and Website Technology in Sukamaju, Tasikmalaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service initiative aims to support the transformation of Sukamaju Village, located in Bantarkalong District, Tasikmalaya Regency, by strengthening the Micro, Small, and Medium Enterprises (MSMEs) sector and utilizing village digital technology. The main issues faced by this village include the lack of business legality such as Business Identification Numbers (NIB), low financial literacy among MSME actors, and the absence of an official digital media platform for promotion and village information. The activities were carried out in four main stages: preliminary, preparation, implementation, and evaluation. The implementation methods included NIB registration socialization for MSMEs in the agro-tourism sector, basic financial literacy training, a seminar on village tourism development, and the provision and training for village website management. The results showed that several MSMEs successfully obtained NIBs, most business actors were able to use simple bookkeeping records, and the Sukamaju Village website was successfully implemented and is now managed by the village apparatus. This community service demonstrates that collaboration between academics and the community can enhance institutional and economic capacity in villages towards digital transformation and local economic independence.